PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT PADA PEMBUATAN KARTU PESERTA JAMINAN KESEHATAN NASIONAL (JKN) DI KANTOR BPJS KESEHATAN KOTA BOGOR - Agus Mantri; Abubakar Iskandar; Irma Purnamasari (LPPM Universitas Djuanda Bogor, 2017)
The increasing number of enthusiasts accessing the BPJS card does not seem to be accompanied with the service of obtaining JKN card (National Health Insurance). Reality people start waiting in front of the office around 6 am just to get early queue. Not to mention the readiness of very minimal service, limited staff and counter and various facilities that do not support the comfort during the wait. Even every day is limited to 90 people. This shows that the quality of service on the manufacture of JKN card in BPJS office has not function properly. The purpose of this study is to know the influence between the quality of service to public satisfaction in the manufacture of JKN card in the office of BPJS Bogor City. The theory used in this research is using the service quality theory of Zeithaml, Parasuraman, & Berry in Ratminto and Atik Septi Winarsih and also the theory of public satisfaction by Boediono which states that to measure a quality of service and a community satisfaction can be measured through five dimensions namely: Tangibles, Empathy, Reliability, Responsiveness, and Assurance (TERRA). The method used is associative with Rank Spearman correlation test. From the correlation coefficient results there are two indicators of the level of influence is very strong that is serving properly and have knowledge while the level of influence on indicators to complete the needs is very low. The results of the contribution of service quality variable to the variable of community satisfaction by 54% are influenced or determined by BPJS service quality variable by 46%. So it can be concluded that Based on the results of associative statistical hypothesis that H0: p = 0 (no relationship) means there is no effect of service quality on community satisfaction.Keywords: Quality of service BPJS, JKN-BPJS program, and community satisfactioncard maker JKN-BPJS.